Answer:
6ab + b^2 - 17a - 4b + 10
Explanation:
-2(a+b-5)+3(-5a+2b)+b(6a+b-8)
Now we break the parenthesis. To break that, we multiply each of the value inside the parenthesis by the adjacent number. That is, for the first part of the expression, we multiply by -2, then by 3, and then by b.
Algebraic Operations need to be considered:
[ (-) x (-) = (+); (-) x (+) = (-)]
= [-(2*a) + (-2*b) - (-2*5)] + [3*(-5a) + (3*2b)] + [(b*6a) + (b*b) - (b*8)]
= -2a - 2b +10 -15a + 6b + 6ab + b^2 - 8b
Now, we will make the adjustment by the similarity value.
= - 2a - 15a - 2b + 6b - 8b + 6ab + b^2 + 10
= - 17a - 4b + 6ab + b^2 + 10
= 6ab + b^2 - 17a - 4b + 10
Therefore, the answer of the expression is = 6ab + b^2 - 17a - 4b + 10